Living through the psychological consequences of COVID-19 pandemic: a systematic review of effective mitigating interventions - Viroj Tangcharoensathien; Angkana Lekagul; Chawisa Suradom; Peeraya Piancharoen; Anamika Chattong (BMJ Open)
Objective This review assesses interventions and their effectiveness in mitigating psychological consequences from pandemic.Method Published English literatures were searched from four databases (Medline, PubMed, Embase and PsycINFO) from January 2020 and September 2021. A total of 27 papers with 29 studies (one paper reported three studies) met inclusion criteria. Cochrane risk-of-bias tool is applied to assess the quality of all randomised controlled trials (RCT).Results All studies were recently conducted in 2020. Publications were from high-income (13, 44.8%), upper middle-income (12, 41.4%) and lower middle-income countries (3, 10.3%) and global (1, 3.5%). Half of the studies conducted for general population (51.7%). One-third of studies (8, 27.6%) provided interventions to patients with COVID-19 and 20.7% to healthcare workers. Of the 29 studies, 14 (48.3%) were RCT. All RCTs were assessed for risk of biases; five studies (15, 35.7%) had low risk as measured against all six dimensions reflecting high-quality study.Of these 29 studies, 26 diagnostic or screening measures were applied; 8 (30.9%) for anxiety, 7 (26.9%) for depression, 5 (19.2%) for stress, 5 (19.2%) for insomnia and 1 (3.8%) for suicide. Measures used to assess the baseline and outcomes of interventions were standardised and widely applied by other studies with high level of reliability and validity. Of 11 RCT studies, 10 (90.9%) showed that anxiety interventions significantly lowered anxiety in intervention groups. Five of the six RCT studies (83.3%) had significantly reduced the level of depression. Most interventions for anxiety and stress were mindfulness and meditation based.Conclusions Results from RCT studies (11%, 78.6%) were effective in mitigating psychological consequences from COVID-19 pandemic when applied to healthcare workers, patients with COVID-19 and general population. These effective interventions can be applied and scaled up in other country settings through adaptation of modes of delivery suitable to country resources, pandemic and health system context.